The causal linkages between sovereign CDS prices for the BRICS and major European economies - Mikhail Stolbov (Kiel Institute for the World Economy (IfW), 2014)
The article examines causal relationships between sovereign credit default swaps (CDS) prices for the BRICS and most important EU economies (Germany, France, the UK, Italy, Spain) during the European debt crisis. The cross-correlation function (CCF) approach used in the research distinguishes between causality-in-mean and causality-in-variance. In both causality dimensions, the BRICS CDS prices tend to Granger cause those of the EU counterparts with the exception of Germany. Italy and Spain exhibit the highest dependence on the BRICS, whereas only India has a negative balance of outgoing and incoming causal linkages among the BRICS. Thus, the paper underscores the signs of decoupling effects in the sovereign CDS market and also supports the view that the European debt crisis has so far had a limited non-EU impact in this market.
Keywords: C50; G10; G15; 330; sovereign credit default swaps (CDS); causality-in-mean; causality-in-variance; European debt crisis; BRICS; decoupling